Opposing FlnA and FlnB interactions regulate RhoA activation in guiding dynamic actin stress fiber formation and cell spreading. (8th February 2017) - Hu, Jianjun; Lu, Jie; Goyal, Akshay; Wong, Timothy; Lian, Gewei; Zhang, Jingping; Hecht, Jonathan L.; Feng, Yuanyi; Sheen, Volney L.
Abstract: Filamins are a family of actin-binding proteins responsible for diverse biological functions in the context of regulating actin dynamics and vesicle trafficking. Disruption of these proteins has been implicated in multiple human developmental disorders. To investigate the roles of different filamin isoforms, we focused on FlnA and FlnB interactions in the cartilage growth plate, since mutations in both molecules cause chondrodysplasias. Current studies show that FlnA and FlnB share a common function in stabilizing the actin cytoskeleton, they physically interact in the cytoplasm of chondrocytes, and loss of FlnA enhances FlnB expression of chondrocytes in the growth plate (and vice versa), suggesting compensation. Prolonged FlnB loss, however, promotes actin-stress fiber formation following plating onto an integrin activating substrate whereas FlnA inhibition leads to decreased actin formation. FlnA more strongly binds RhoA, although both filamins overlap with RhoA expression in the cell cytoplasm. FlnA promotes RhoA activation whereas FlnB indirectly inhibits this pathway. Moreover, FlnA loss leads to diminished expression of β1-integrin, whereas FlnB loss promotes integrin expression. Finally, fibronectin mediated integrin activation has been shown to activate RhoA and activated RhoA leads to stress fiber formation and cell spreading. Fibronectin stimulation in null FlnA cells impairs enhanced spreading whereas FlnB inhibited cells show enhanced spreading. While filamins serve a primary static function in stabilization of the actin cytoskeleton, these studies are the first to demonstrate a dynamic and antagonistic relationship between different filamin isoforms in the dynamic regulation of integrin expression, RhoGTPase activity and actin stress fiber remodeling.